If (-5,1)(−5,1) and (11,13)(11,13) are diameter endpoints then the center of the circle is at the midpoint between them:
Center at ((-5+11)/2,(1+13)/2)=(color(blue)3,color(red)7)(−5+112,1+132)=(3,7)
The radius is the distance from the center, (3,7)(3,7) to a diameter endpoint (I will use (11,13)(11,13) but either should work).
By Pythagorean Theorem
Radius = sqrt((11-3)^2+(13-7)^2)=√(11−3)2+(13−7)2
color(white)("XXX")=sqrt(8^2+6^2)XXX=√82+62
color(white)("XXX")=sqrt(64+36)XXX=√64+36
color(white)("XXX")=sqrt(100)XXX=√100
color(white)("XXX")=color(green)(10)XXX=10
The center-radius form for a s circle with center at (color(blue)a,color(red)b)(a,b) and radius color(green)rr is
color(white)("XXX")(x-color(blue)a)^2+(y-color(red)b)^2=color(green)r^2XXX(x−a)2+(y−b)2=r2
Using the derived values
color(white)("XXX")(x-color(blue)3)^2+(y-color(red)7)^2=color(green)10^2XXX(x−3)2+(y−7)2=102
Here's a graph of (x-3)^2+(y-7)^2=10^2(x−3)2+(y−7)2=102 for verification purposes: